Measuring gut perfusion and blood flow in neonates using ultrasound Doppler of the superior mesenteric artery: a narrative review - Murphy, C.; Baskind, S.; Aladangady, N.; Banerjee, J. (Frontiers in Pediatrics, 2023)
The gut is a relatively silent organ in-utero but takes on a major role after birth for absorption and digestion of feed for adequate nutrition and growth. The neonatal circulation undergoes a transition period after birth and gut perfusion increases rapidly to satisfy oxygen demand and consumption. If this process is compromised at any stage, preterm and Fetal Growth Restricted (FGR) infants are at particular risk of gut tissue injury secondary to hypoxia, leading to Necrotising Enterocolitis (NEC). Feeding can also be a challenge in these high-risk groups due to gut dysmotility. SMA doppler is a safe, bedside investigation which could rapidly aid clinicians with feeding strategies and in monitoring high risk infants. This article aims to establish normal patterns of gut blood flow velocity (BFV) in neonates using SMA doppler, and reviews how it might be used clinically in pathologic states.